Most érdemesebb Budapest repülőteréről, mint Magyarország nemzeti légitársaságának jövőjéről gondolkodni - Gál, József (Jelenkori Társadalmi és Gazdasági Folyamatok, 2013)
There is a big change in Hungary about air services. We lost our Hungarian national airlines called MALÉV and the role of Budapest Airport has been changing. The national airline is definitely emblematic company for a country. Welcome to the traveler, announces the country’s existence, presence arouses the interest and invites travelers. Malév was such a company with its typical painting, staff uniforms and kindness. It was the mediator of the Hungarian hospitality to foreigners. It is difficult to describe the feeling - which I also experienced a number of cases - when a Malév aircraft landed at a foreign airport, you could feel a little bit when we are home. Is a national airline to be just business issue, or more? In my paper - politics-free - I would like to describe termination of some media reaction to the team but not limited to. Suddenly, many people said their opinion, such a sound with a professional. The picture is very colorful and free of any emotion. We can not forget also that although it was a business-driven enterprise, which, however, was more than just an enterprise. It is interesting how to find new role of Budapest Airport.